Implementasi Sistem Informasi Perpustakaan Di SDN Sirnajati 01 Berbasis VB.Net - Yoga Religia; Bella Yoviana Hardini (Jurnal SIGMA, 2018)
The development of technological advances in all fields, the use of computers is very helpful, both in the fields of education, trade, industry and health. One sector in the field of education that is currently developing a computerized system is school. School is a formal education to provide knowledge for children. In a school many students need additional lessons or more knowledge, one of them through the library. Research with the title "LIBRARY INFORMATION SYSTEMS IN VB.Net BASED SIRNAJATI 01 Elementary School", has a formulation of the problem of how to design and build a system that can assist library officers in recording, or managing books in the library. Because in the library in Sirnajati 01 Elementary School, still using the manual method. To obtain the required data during writing, several methods are used, including: interviews, observation, and literature. The data obtained is then analyzed and described using SDLC development methods that are object oriented such as UML (Unified Modeling Language). The tools for making this application the author uses the Visual Basic.Net programming language, then for the database using XAMPP. The results of the expected research system that has been made can help the performance of library officers better.